The Spirit Of Water Practices of cultural reappropriation. Indigenous heritage sites along the coast of the Eastern Cape-South Africa - Minguzzi, Magda (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2021)
This book describes a research project begun by the author in 2015 and co-authored by the chiefs of the KhoiSan peoples living in the Nelson Mandela Bay Municipality, South Africa, aided by staff and students at Nelson Mandela University. The scope of the project was to investigate methods and procedures that could help re-establish the link between the Indigenous communities and their 'forgotten' heritage sites due to the colonial segregations. Making use of a participatory and interdisciplinary method we explored the tangible and intangible heritage of the Eastern Cape province, with particular attention to the remains of precolonial fish traps located along the shoreline. Included also are important testimonies from the KhoiSan chiefs who, alongside the author, led the project.